Ethical mindsets - Issa, Theodora; Pick, David (NOVA Publication, 2012)
The main aim of the chapter is to discuss the theoretical background and outcomes of recent research on ethical mindsets. In recent times there have been increased calls from practitioners, academics, heads of state, and heads of international organizations to examine the ethics of businesses in an attempt to prevent the transgressions which have led to the ongoing crises affecting global markets and society. Ghoshal (2003) argues that researchers in management should share the blame for failures such as these. Alzola (2008) questions whether virtue ethicists need to abandon the very enterprise of building a character, based on moral theory in business ethics and organizational behaviour. Jones (2010) argues that the latest financial crisis had set off emotions, and much breast-beating about ethical behaviour, calling for the examination of the business moral compass. Alzola (2011) investigates the relationship between business and ethics in academic research, examining the status of the ‘separation’ and the ‘integration’ theses and calls for a reconciliation of normative and descriptive approaches and methods of research in business ethics. There is a need therefore to move beyond current methods and concepts of research. To this end, this chapter provides new perspectives on such research with particular attention being paid to aesthetics, spirituality and ethical mindsets.